The inorganic carbon source and concentration affect growth and central metabolism in a microcystin producer cyanobacteria - Castro, Naira Valle de (2019)
Cyanobacteria, microorganisms belonging to the Bacteria domain, are widely distributed geographically, yet most genera are found in freshwater environments. Some cyanobacterial strains are able to produce toxins (cyanotoxins), like microcystins (MCs), that show hepatotoxic effect in animals. The genetic basis, chemical structure, and biosynthetic route as well as microcystin action in eukaryotic organisms have been deeply studied. However, it remains unknown which are the roles played by such compounds in the producing organism. Here, we tested the hypothesis that growth medium supplied with different concentrations of inorganic carbon (Ci) source promotes metabolic and physiological adjustments coupled with changes in MC production. To this end, the cyanobacterial strain Scytonemataceae CCM-UFV057 was cultured in different growth medium, (i) standard BG-11 0 (supplied with 0.02 g·L - of sodium carbonate), as control; (ii) BG-11 0 without Ci (T1); and (iii) BG-11 0 supplied with two concentrations of sodium bicarbonate, 0.016 g·L -1 (T2) and 1.6 g·L -1 (T3). Growth evaluation together with physiological and biochemical analysis as well as MC’s quantification were carried out. Growth parameters of CCM-UFV057 were similar for all growth conditions. Both T1 and T2 lead to similar metabolic patterns, despite different responses in both photosynthetic and respiratory rates. The strain CCM-UFV057 was able to produce five MCs congeners, with the variants showing m/z of 540 and 1037 as the most abundant forms in all conditions. MCs production was highly influenced by Ci concentration, and T1 and T3 lead to the higher and lower MC concentration, respectively, indicating that low Ci concentrations somehow improve the MC production. Notably, the carbon source (carbonate versus bicarbonate) did not seems to affect MC production. Taken together, our data suggest that high amounts of MC under low Ci conditions can contribute to the maintenance of photosynthetic rates, keeping both higher carbon assimilation rates and cellular homeostasis without growth impairments.